The Artificial Intelligence Implementation in Nursing Services: Literature Review - Widiyono, Widiyono; Sumarni, Ranti Ningsih (STIKep PPNI Jawa Barat, 2025)
Backgroud : Major changes to clinical practice are likely to occur as a result of the introduction of AI into the healthcare industry. Virtual assistants (e.g., AI documentation tools such as Nuance DAX and AI-enabled medical diagnostic tools) are one of the ways artificial intelligence has been applied in our daily lives; one example is its use in the documentation process in the nursing profession. However, there are concerns about false data and possible unintended effects on patients when AI is used in nursing care. In addition, there is only 2% research on AI and its potential benefits for nurses. There is a need for more in-depth research on the use of AI in nursing care. Aims : This study to review the findings and evidence base related to the use of artificial intelligence (AI) in nursing care. Methods : The research approach used was a literature review. Articles on the use of AI in nursing care were searched using topics and keywords related to nursing, artificial intelligence, and nursing care. Relevant research was searched using the Boelean formula and filtered for articles published between 2019 and 2024, including PUBMED, Scopus, and Google Scholar. Research involving the creation or verification of artificial intelligence (AI)-based technologies used in nursing care was considered for inclusion, as were research designs that included experimental or observational methods and quantitative or qualitative data analyses, or a mixture of both. The retrieved articles were screened and discussed according to the research criteria. Results : The results of this study obtained 10 articles that met the criteria and met the requirements (out of a total of 2,490 publications) which were then discussed. The articles discussed the use and application of AI in nursing services for both clinical and academic purposes. Conclutions : There are many potential advantages to implementing AI into nursing services, but they must be carefully considered. To overcome these barriers to the use of AI to improve nursing services, further research is needed. In the future, nurses need to be technologically literate